2019
DOI: 10.1186/s13049-019-0596-4
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis: mechanisms of bacterial injury to the patient

Abstract: In bacteremia the majority of bacterial species are killed by oxidation on the surface of erythrocytes and digested by local phagocytes in the liver and the spleen. Sepsis-causing bacteria overcome this mechanism of human innate immunity by versatile respiration, production of antioxidant enzymes, hemolysins, exo- and endotoxins, exopolymers and other factors that suppress host defense and provide bacterial survival. Entering the bloodstream in different forms (planktonic, encapsulated, L-form, biofilm fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(106 citation statements)
references
References 263 publications
(272 reference statements)
0
104
0
2
Order By: Relevance
“…30 In this case, pathogens can directly reach the systemic circulation and cause catheter-related blood stream infection (CR-BSI) 31 or travel to various organs and induce organ failure. 32 Nosocomial infections would be widespread and would be important contributors to morbidity and mortality. This has public health implications causing increasing economic and human health impact.…”
Section: Discussionmentioning
confidence: 99%
“…30 In this case, pathogens can directly reach the systemic circulation and cause catheter-related blood stream infection (CR-BSI) 31 or travel to various organs and induce organ failure. 32 Nosocomial infections would be widespread and would be important contributors to morbidity and mortality. This has public health implications causing increasing economic and human health impact.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Maître et al showed that diapedesis of neutrophils is at least partly dependent on ATP-P2X1 interaction [102]. It is therefore conceivable that ATP secreted by bacteria in the blood stream or by bacteria bound to platelets or erythrocytes [103] favors extravasation of leukocytes. Furthermore, it is well known, that some bacteria are able to survive within phagocytes and, therefore, these mechanisms could be exploited by some bacteria for its own dispersal throughout the body [104].…”
Section: Bacterial Atp As Potential Virulence Factor In Inflammationmentioning
confidence: 99%
“…Erythrocytes play an important role in human innate immunity. Bacteria in the bloodstream can be attracted and kept by erythrocytes and killed by oxidation [23,24]. There is no doubt that erythrocytopenia would undermine the protective mechanism.…”
Section: Discussionmentioning
confidence: 99%